The Maternal Subject in the Budding Britsih Novel: Considering Daniel Defoe's Fiction - Vahaviolos Valassis, Anastasia (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
This article attempts to create a three-part structure in which it can situate its more particular discussion of maternal subjectivities in the work of Daniel Defoe. In the first part, it looks at the British novel’s relationship to the representation of human subjectivity. It discusses the connection to the nonfictional form of the autobiography as well as to ideologies of individualism. The article argues that representing maternal subjectivity in fiction poses a unique challenge to the British novel’s form: the healthy relationality of the maternal subject is suppressed generically, as narrative requires a dominant character through which to create meaning. The second part looks at Defoe’s three major novels—Robinson Crusoe, Moll Flanders, and Roxana—and how the prefaces instruct the reader about how to receive the scandalous stories about these mother figures. This overview highlights Defoe’s interest in writing the gendered “other” and his difficulty in depicting a subjective relationality in Roxana without novelistic tragedy and narrative collapse. The third part involves a deeper reading of Moll Flanders, in which moments of Moll’s maternal inclinations are read against the larger picture of her denial of maternal obligations. Moll’s is a damaged child’s subjectivity, one that still craves a mother’s care, approval, and affection. The narrative structure requires that she stake a rhetorical claim that excises the subjectivities of others from the story. In concluding, the article argues that it is valuable to read Defoe’s early experiments with the formation of the maternal subjectivity in fiction because they show a sensitive awareness of the factors that enable the composition and transmission of maternal narrative within the genre of the novel.